INFLUENCE OF HYDROXYPROPYL-β-CYCLODEXTRIN ON REPAGLINIDE RELEASE FROM SUSTAINED RELEASE BIOADHESIVE BUCCAL TABLETS - K, Harika; K, Sunitha; Kumar P, Pavan; Y, Madhusudan Rao (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: The purpose of this investigation was to study the influence of cyclodextrin complexation on development of sustained release bio-adhesive repaglinide tablets for buccal delivery. Methods: Based on preliminary phase solubility studies, solid complexes prepared by freeze-drying method in 1:1 molar ratio were selected and characterized by Fourier transform infrared spectroscopy to corroborate the fact of complex formation. The sustained release repaglinide tablets were produced by direct compression and this drug or complexed –loaded hydrophilic matrices using HPMC, Sodium CMC and Carbopol as muco-adhesive polymers were assessed for in vitro bioadhesion strength, in vitro release modulation, surface pH, % moisture absorption and ex vivo permeation through porcine buccal membrane. Results: When the drug was incorporated as repaglinide-Hydroxypropyl-β-Cyclodextrin (HP-β-CD) freeze-dried product, total amount of drug permeated from the tablet through epithelium in about 12 hrs, displaying a constant release regimen after a transient period. The effect of HP-β-CD incorporation on the release mechanism was rationalized on the basis of the interplay of different physical phenomena: erosion and swelling of the tablet, drug dissolution, and complex formation. Formulation F10 showed % moisture absorption of 23.46 for 4hrs, surface pH 6.9±0.015, Peak detachment force 3.65±0.18 N, Work of adhesion 1.12±0.10 mJ, and in vitro drug release 98.31% in 6h. The feasibility of buccal administration of repaglinide was assessed by permeation experiments on excised mucosa of pig. The ex vivo permeation studies demonstrated that the matrix tablets containing repaglinide–HP-β-CD (F10) solid complex exhibited significantly higher drug permeation (92.18 % for 12hrs) compared to all of the other formulations tested, which could be attributed to both, the presence of the polymers, and the drug-cyclodextrin complexation. The flux was found to be increased by 1.12-1.37 folds with a permeability coefficient of 0.017-0.018. Conclusion: The results demonstrate that the formulations with inclusion complexes afford high utility as a trans-mucosal drug delivery system for improved drug release and permeability. KEY WORDS: Repaglinide, Freeze drying, HP-β-CD complexation, Bioadhesion, Ex-vivo permeation, Solubility